The impact of a tournament approach on environmental performance: the case of air quality disclosure in China. Issue 18 (15th April 2021) - Tan, Jianhua; Tan, Zhidong; Chan, Kam C.
ABSTRACT: We examine the effect of air quality tournament over the 2012–2016 period on city – and firm-level environmental performance in China. We document that government officials and firm managers of tournament cities change their behavior and make more environmental investments (EIs) than those of non-tournament cities. Additional analysis suggests that the increase in EIs is primarily driven by cities that have previously been ranked last in the tournament. Hence, government official and manager behavior become more pro-environment after the implementation of the air quality tournament. Furthermore, when there is a large grassroots participation, local media reporting, or when the official is motivated to promotion, the impact of tournament participation on EIs is magnified, implying pro-environment behavior changes become more salient when there are outside pressure or strong official incentives. Most importantly, we find the tournament cities experience better air quality than non-tournament cities. Policy implications are discussed.